One Rule to Rule Them All: Subordinate Legislation and the Law of Judicial Review - Mancini, Mark (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2023)
The Supreme Court’s decision in Vavilov purported to provide a complete rule regime for the review of administrative action, simplifying an area of the law subject to erratic doctrinal amendment. One question, post-Vavilov, is how far this rule regime sweeps.For some time, Canadian courts have struggled to review subordinate legislation — executive regulations, municipal bylaws, and other binding rules. At some points, courts have suggested that this sort of legislation should be reviewed highly deferentially such that only a regulation completely unrelated to an enabling statute would be ultra vires. At other times, courts have simply applied the run-of-the-mill reasonableness standard, which governs adjudicative decisions, to municipal bylaws and other binding rules. This confusion has only proliferated after the Supreme Court’s rejigging of the law of judicial review in Vavilov, and courts have since struggled to determine whether Vavilov, which sets a presumptive standard of reasonableness for all administrative action, applies to subordinate legislation.This paper argues that Vavilov’s rule regime, whatever its flaws, provides a set of constitutionally compliant rules that are workable in the context of subordinate legislation, including executive legislation. It argues that Vavilov’s simplifying mission should be construed broadly. By centring the institutional design choices of legislatures, Vavilov connects to the legitimate constitutional source of subordinate legislation: its attachment to a statute adopted in the primary lawmaking act. This core feature of Vavilov makes it transferable, if imperfectly, to the context of subordinate legislation. It also makes Vavilov an attractive starting point for other areas of the law of judicial review.